Workplace Communication: Categories, Obstacles, and Approaches for Enhancement - Kamalpreet Khattra; Rahul Sangwan (Journal of Advanced Research in Journalism & Mass Communication, 2024)
Communication is an integral part of human life. Communication can be cited as a process through which an individual can share their ideas, thoughts, feelings, suggestions, and ideas with others. Communication could be effective only when everyone involved in that discussion can express themselves and understand every idea from that conversation clearly. The foundation of every organized and structured action in any organization is the business communication process and communication strategy. Effective corporate communication at work is essential to forming and preserving working relationships in organizations. Communication at the workplace is mainly formal, but people get involved in informal communication too, which sometimes leads to inefficiency of actions. Even the use of non-verbal communication is as impactful as verbal communication because it helps in building trust among colleagues as well as management and staff. Even the usage of non-verbal communication is as impactful as verbal communication as it helps to build trust among colleagues as well as management and staff, although people face difficulties in the same. The efficiency of conversation at work can also be enhanced if people develop soft skills in them. This article will provide a review of the communication process, hurdles to communication, and guidelines for administrators on how to improve communication efficacy.